Pendidikan, Penyakit Kronis dengan Perilaku Perawatan Pra Konsepsi di Kabupaten Kudus - Nailufar, Yuyun; Hidayah, Noor; Suwarto, Tri (Innovative: Journal Of Social Science Research, 2025)
Preconception care is a strategic step to prepare for a healthy pregnancy and reduce the risk of complications for the mother and fetus. This study aims to analyze the relationship between education level and chronic diseases with preconception care behavior among women of childbearing age (WUS) in Kudus Regency. The study design used a quantitative approach with a survey method. A sample of 100 WUS was determined using the Slovin formula and purposive sampling technique based on certain criteria, such as marital status and pregnancy plans. Data were collected through a questionnaire that had been tested for validity and reliability, and analyzed using the Chi-square test. The results of the analysis showed no significant relationship between education level (p = 0.336) and chronic diseases (p = 0.441) with preconception care behavior. Although descriptively there was a trend of better preconception behavior in women with higher education and without chronic diseases, the relationship was not statistically significant. These findings indicate that education and chronic diseases are not the sole determinants of preconception behavior, so it is necessary to consider other factors such as family support, access to information, and health services. This study recommends the need for a holistic approach in promoting preconception care to improve pregnancy readiness at the community level.